Phytochemical study and evaluation of the antimicrobial activity and cytotoxicity of Cuscuta racemosa - Ferraz,Helena O. (2011)
Cuscuta racemosa Mart. is a parasitic plant of the Convolvulaceae family, used in popular medicine as an anti-inflammatory and a diuretic, for stomach and hepatic disorders, and for treating fresh wounds. This plant is popularly known as "cipó-chumbo" and "fios-de-ovos". In this study, it was chemically investigated and tested for its antimicrobial activity and cytotoxicity. The flavonoid and tannin content of the dried plant were 2.79% and 2.01%, respectively. Furthermore, the 4'-methoxyquercetin flavanoid compound was isolated from the ethanolic fraction. The minimum inhibiting concentration in the antimicrobial test was 2.0 mg/ml for Staphylococcus aureus, and a DL50 of 0.231 mg/mL was obtained in the cytotoxicity experiment. The fraction directed to alkaloids was able to eliminate 100% of the brine shrimp used for the test.